Knowledge, attitudes, and practices of influenza and pneumococcal vaccines among agricultural workers: results of an Italian a cross-sectional study - Riccò, Matteo; Vezzosi, Luigi; Gualerzi, Giovanni; Odone, Anna; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2019)
Background: Working age is increasing across Europe. Seasonal influenza (SID) and pneumococcal disease (PND) immunization programmes might be successfully implemented at the workplace. We conducted a cross-sectional survey among to assess SID and PND vaccine status, as well as knowledge, attitudes and practices (KAP) in a representative sample of agricultural workers (AWs) aged ≥55 years in North-Eastern Italy. Methods: A structured questionnaire was administered in person by trained personnel. Bivariate and multivariate logistic regression analyses were carried out to identify behavioral and work-related factors associated with SID and PND vaccine uptake. Results: Among 707 participants, 238 were aged 55 years or more (33.7% of total). Of them, 39.1% had an up-to-date immunization status towards influenza, and 17.6% towards pneumococcus. Factors associated with inadequate immunization were doubts about influenza vaccine safety (40.0%) and the confidence in natural immunity towards pneumococcus (30.8%). Attitude towards vaccinations was somehow favorable in 44.5% of participants for SID, and 37.8% for PND. Overall, 37.4% and 21.8% workers were aware of national recommendations on SID and PND immunization, respectively. This factor was characterized as a significant predictor for SID vaccination (multivariated Odds Ratio, OR 32.688 95%CI 12.015-88.930), as well as the perception of SID as a severe disease (OR 7.539 95%CI 3.312-17.164), and the perceived value of preventing new infections (OR 3.215 95%CI 1.205-8.578). A somehow favorable attitude towards vaccinations was the main predictor (OR 39.214 95%CI 10.179-151.1) for PND vaccination. Conclusions: Our study indicates that older workers lack appropriate knowledge of national recommendations and correct risk perception of SID and PND infections, but also vaccines’ side effects. As the latter has been recognized as predictive factor for SID vaccination, our results stress the importance for tailored informative interventions in the workplaces aimed to increase risk perception and vaccine acceptance. (www.actabiomedica.it)